Dual-responsive aggregation-induced emission-active supramolecular nanoparticles for gene delivery and bioimaging. Issue 51 (2nd June 2016) - Dong, Ruijiao; Ravinathan, Screenath P.; Xue, Lizhe; Li, Nan; Zhang, Yingjian; Zhou, Linzhu; Cao, Chengxi; Zhu, Xinyuan
Abstract : Dual-responsive aggregation-induced emission-active supramolecular nanoparticles exhibit a unique morphological transition with fluorescence variation, further achieving efficient gene delivery and bioimaging. Abstract : Dual-responsive aggregation-induced emission-active supramolecular fluorescent nanoparticles are reported, which have the ability to undergo a unique morphological transition combining with a cooperative optical variation in response to pH and light stimuli. The dynamic supramolecular nanoparticles show excellent biocompatibility and effective plasmid DNA condensation capability, further achieving efficient in vitro gene delivery and bioimaging.